REDAMAN GETARAN LANTAI GEDUNG BERTINGKAT MENGGUNAKAN BAJA WF - Immanuel Panusunan Tua Panggabean (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2018)
Vibrations on the floor plates of multi-storey buildings can occur due to excitation arising from the activities of human activity such as running, dancing and other sports. Vibrations become excessive on the multi-storey building floor system, and this vibration is not related to the building's safety factor, but only in contact with the user's inconvenience. Excessive vibrations occurring in the system of floor plate structure may occur in multi-storey buildings that have (1) lightweight floor structure systems due to the use of high-grade building materials or composite materials on building structural elements such as beams that allow the design of the elements of the structure (2) long-stretched floor plate system with low structural stiffness in which the dominant natural floor frequency tends to be low and close to excitation frequency, and (3) the floor plate structuring system has a low damping value due to the use of the partition and fewer furniture items. The three things mentioned above cause the vibration on the floor plate system to be excessive and cause discomfort and disruption for users of the building. Vibration on the floor plate system causing the discomfort may occur on a floor plate system that has a vibration frequency (fn) of less than 8 Hz. To reduce the vibration frequency (fn) of the plate system must be increased to approximately 8 Hz natural frequency. The use of WF-shape steel structure used is WF 200, capable of increasing the damping value in the system of floor plate structure which is observed in one of the school buildings in Medan.